Pengaruh Penambahan Plastik LDPE Pada Campuran Aspal Beton Lapis AC-BC - Hidayati, Hilda Nur; Rifqi, Mirza Ghulam; Amin, M. Shofi’ul (Indonesian Society of Applied Science, 2021)
Increased traffic volume growth has an impact on demand for the construction of pavement structures and the use of materials used. Therefore, we need a material that can help coat aggregate materials other than asphalt in order to reduce these effects, for example polymer or plastic materials. One effort that can be done is to modify the effect of adding Low Density Poly Ethylene (LDPE) plastic as an additive in AC-BC (Asphalt Concrete-Binder Course) asphalt mixture. The purpose of this study was to determine how the effect of the addition of Low Density Poly Ethylene (LDPE) type plastics as an added ingredient of AC-BC hot asphalt mixture on Marshall characteristics. Tests conducted include aggregate testing, asphalt testing, plastic testing, and Marshall testing. The design of the mixture is done by dry (dry process) using a variation of plastic content of 0%, 2%, 3%, and 4% with each bitumen content of 4.5%, 5%, 5.5%, 6.0 % and 6.5%, the number of test specimens made is 75 test specimens. From the Marshall test results obtained KAO value of 6.5% with a variation in LDPE plastic content of 3%. With a stability value of 1878.40 kg, a flow value of 3.81 mm, an MQ value of 472.5 kg / mm, a VFB / VFA value of 72.55%, a VIM value of 4.29%, and a VMA value of 17.74%.